2014
DOI: 10.1111/1750-3841.12491
|View full text |Cite
|
Sign up to set email alerts
|

GC‐MS‐Based Metabolite Profiling of Cosmos caudatus Leaves Possessing Alpha‐Glucosidase Inhibitory Activity

Abstract: GC-MS and multivariate data analysis was applied to discriminate Cosmos caudatus samples extracted with water and different ratio of ethanol. Orthogonal partial least-squares (OPLS) model developed was used to determine the major metabolites contributed to α-glucosidase inhibitory activity. This approach also has the ability to predict the bioactivity of a new set of extracts based on a developed validated regression model that is important for quality control of the herb preparation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
76
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 67 publications
(97 citation statements)
references
References 27 publications
18
76
0
Order By: Relevance
“…This finding might be due to the ability to dissolve metabolites that contribute to α-glucosidase inhibition activity. This result was in contrast with a previous study, which reported that absolute ethanol and methanol had the highest bioactivity compared to aqueous solvents [18]. The α-glucosidase inhibition activity are consistent with the TPC and DPPH results, wherein FD exhibited the highest TPC and antioxidant activity, and OD showed the lowest values for both.…”
Section: Effect Of Drying Methods and Solvent On α-Glucosidasesupporting
confidence: 55%
See 1 more Smart Citation
“…This finding might be due to the ability to dissolve metabolites that contribute to α-glucosidase inhibition activity. This result was in contrast with a previous study, which reported that absolute ethanol and methanol had the highest bioactivity compared to aqueous solvents [18]. The α-glucosidase inhibition activity are consistent with the TPC and DPPH results, wherein FD exhibited the highest TPC and antioxidant activity, and OD showed the lowest values for both.…”
Section: Effect Of Drying Methods and Solvent On α-Glucosidasesupporting
confidence: 55%
“…However, the absolute solvent exhibited lower activity compared to 80 % solvent extracts. According to previous studies, adding water to the solvent at a low quantity enhances its antioxidant activity [3,18]. In light of these findings, P. niruri could be used in medicinal applications with a high therapeutic value.…”
Section: Effect Of Drying Methods and Solvent On The Antioxidantmentioning
confidence: 87%
“…Javadi et al . () reported that α‐glucopyranoside, succinic acid, octadecanoic acid, α‐linolenic acid, D‐fructose, propenoic acid and valine from Cosmos caudatus leaves were effective at accelerating α‐glucosidase inhibitory activity. This result is also consistent with our findings given the abundant presence of all of these compounds in P. macrocarpa plant extracts.…”
Section: Resultsmentioning
confidence: 99%
“…The percentage of yield of the ethanol extract was found to be 10%, which is the lowest yield. This result indicates that the extraction yield depends on the solvent polarity where the more polar solvent gives the higher yield (Javadi et al, ). The results demonstrated that water was the most suitable extraction solvent according to the extract's yield.…”
Section: Resultsmentioning
confidence: 97%
“…The extracts were prepared according to the method of Javadi et al () with some modifications. The extractions were performed by using two solvents, ethanol, and water, at various ratios (100% ethanol, 80% ethanol, 60% ethanol, 40% ethanol, 20% ethanol, and 0% ethanol) with six replicates.…”
Section: Methodsmentioning
confidence: 99%